\(y\ne0\)ta có: \(\hept{\begin{cases}x^2+y^2+xy+1=4y\\y\left(x+y\right)^2=2x^2+7y+2\end{cases}\Leftrightarrow\hept{\begin{cases}\frac{x^2+1}{y}+x+y=4\\\left(x+y\right)^2-2\frac{x^2+1}{y}=7\end{cases}}}\)
Đặt \(u=\frac{x^2+1}{y};v=x+y\)ta có hệ \(\hept{\begin{cases}u+v=4\\v^2+2v-15=0\end{cases}\Leftrightarrow\hept{\begin{cases}u=4-v\\v^2+2v-15=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}v=3;u=1\\v=-5;u=9\end{cases}}}\)
Với v=3; u=1 ta có hệ \(\hept{\begin{cases}x^2+1=y\\x+y=3\end{cases}\Leftrightarrow\hept{\begin{cases}x^2+1=y\\y=3-x\end{cases}\Leftrightarrow}\hept{\begin{cases}x^2+x-2=0\\y=3-x\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=1;y=2\\x=-2;y=5\end{cases}}}\)
Với v=-5;u=9 ta có hệ \(\hept{\begin{cases}x^2+1=9y\\x+y=-5\end{cases}\Leftrightarrow\hept{\begin{cases}x^2+1=9y\\y=-5-x\end{cases}\Leftrightarrow}\hept{\begin{cases}x^2+9x+46=0\\y=-5-x\end{cases}}}\)(hệ này vô nghiệm)
Vậy hệ đã cho có nghiệm (x;y)={(1;2);(-2;5)}